Strategi Marketing Produk Mi Lemonilo Di Instagram Menggunakan GRUP K-POP NCT Dream Sebagai Brand Ambassador - Khuyaimah; Hamidah; Muslimin (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
One of the marketing strategies used by companies today is digital marketing through Instagram social media, there are factors to influence reciprocal behavior towards marketing products, one of which is the presence of Korean culture that enters Indonesia. From this phenomenon, several companies in the industrial business field are competing to attract public attention by bringing Korean artists to carry out potential collaborations through product marketing. Lemonilo officially announced the form of his product collaboration with a boy band from South Korea, namely NCT ​​Dream as Lemonilo's brand ambassador. This study aims to find out (1) How is the "Mi Lemonilo" strategy using NCT Dream as a brand ambassador for product marketing? (2) Did the use of the Korean artist "NCT Dream" as a brand ambassador really attract the attention of the audience, especially via Instagram? The method used in this study uses a qualitative method with the analysis of the AISAS method. The data were taken in the form of observation and documentation interviews with 5 informants from NCT Dream fans in Palembang, and supported by data sources taken through journals and the internet. The results showed (1) the marketing strategy of Lemonilo X NCT Dream succeeded in increasing the company's image, and making fans interested in Lemonilo products. (2) The use of Korean artists as brand ambassadors can attract an audience on Instagram as a media marketing strategy by getting an increase in the number of followers, collaboration products that are displayed through Instagram posts can be sold quickly, share information about this collaboration between fans, and share their experiences through social media by NCT ​​Dream fans.